Central Anticholinergic Syndrome Following Excessive Mydriatic Use in an Eight-Year-Old Patient - Nazan Kaymaz; Mehmet Erdem Uzun; Fatih Battal; Yusuf Güzel; Hakan Aylanç (Trends in Pediatrics)
Cyclopentolate hydrochloride, belonging to a class of drugs known as anticholinergics, is an ophthalmic solution frequently used in ophthalmology clinics because of its cycloplegic and mydriatic effects in both refractions as well as fundus examinations. After application, the maximum cycloplegic effect begins approximately after 30-60 min, which can further continue up to 24 h. Due to a dose-dependent relationship, cyclopentolate hydrochloride’s side effects can be observed both in an ocular and systemic manner which may occur if solutions more than 0.5% concentration are used. Herein, we report central anticholinergic syndrome due to the administration of excessive amounts of cyclopentolate hydrochloride in a child.